Implementasi Dan Analisis Motion Graphic Quality Awareness Sebagai Media Informasi Di PT. Infineon Technologies Batam - Selly Artaty Zega; Harish Manarul Fauzi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2022)
Along with developments and advances in technology, industries need information media to increase their production by optimizing human resources. One of the information media that can be used is motion graphics. Therefore, the problem in this study is to implement awareness of the quality of motion graphics as an information media at PT. Infineon Technologies Batam and to find out the effect of motion graphics on changes in employee performance on quality awareness of information media. In this final project, the method of multimedia development is Villamil–Molina. Analyzing the motion graph is a quantitative method using the EPIC model. Respondents in this study arie employees of PT. Infineon Technology Batam. The results of this final project will be in the form of motion graphics in MP4 format as a media of quality awareness information and the analysis of employee interest in motion graphics quality awareness based on the motion graphics produced.